Nasotracheal prolonged safe extubation in acute respiratory failure post-thyroidectomy: An efficacious technique to avoid tracheotomy? A retrospective analysis of a large case series. (May 2017) - Ferraro, F.; Gambardella, C.; Testa, D.; Santini, L.; Marfella, R.; Fusco, P.; Lombardi, C.P.; Polistena, A.; Sanguinetti, A.; Avenia, N.; Conzo, G.
Abstract: Background: Acute respiratory failure is a rare life threatening complication following thyroid surgery and its incidence is reported as high as 0.9%. Clinical presentation of severe acute respiratory failure is characterized by dyspnea, inspiratory airways distress, hypoxia and its standard current management is the orotracheal intubation and safe extubation. In case of persistent distress, tracheotomy is mandatory. The Authors, analysing a large acute respiratory failure clinical series, describe an innovative treatment of this severe condition: the nasotracheal prolonged safe extubation. Methods: Patients treated at our Intensive Care Unit for acute respiratory failure following thyroid surgery from January 2004 to December 2013, were reviewed. Demographic data including gender, age, clinical presentation, laryngoscopic findings, management and outcome during a 24-months follow-up after treatment were collected and evaluated. Moreover, the strategy for prolonged nasotracheal safe extubation was carefully described. Results: Nineteen out of the 2853 patients scheduled for thyroid surgery (0.66%) at our University Hospital, developed post-operative acute respiratory failure. All of them were treated by nasotracheal prolonged safe extubation. The success rate in avoiding highly invasive treatment was of 84.2%, since only 3 patients needed definitive tracheotomy (15.7%). Conclusions: In our series, the prolonged safe extubation reduced the almost totality of expected tracheotomies in patients with acute respiratory failure following thyroid surgery (84.2%), demonstrating its feasibility and efficacy. It was a well tolerated and minimal invasive procedure that allowed a good respiratory ability and a fast clinical resolution of the laryngeal functional impairment. Highlights: An innovative technique to manage postoperative acute respiratory failure. Prolonged safe extubation allow a good respiratory ability and a fast clinical symptoms resolution. In our series the prolonged safe extubation success rate was 84.2%.